Assessment of skills training in the Community Work Programme of Erasmus. - Mogakane, Kgothatso Selby (My University, 2015)
Skills training is one of the key pillars of development that was identified during the new democratic dispensation, post 1994. It was affirmed that political freedom would not be meaningful without active participation by people in the economy through job opportunities. Government has since 1994 introduced various economic programmes to address the triple challenges of inequality, poverty and unemployment. Skills training and development was the key driver in those programmes. In 2009 government introduced the Community Work Programme (CWP) in a bid to address unemployment. Central to its objectives, was skills training and development for participants of the programme. This was crucial to ensure a skilled and empowered workforce that would be able to contribute towards the development of the economy when trainees exit the programme, either because of better job opportunities or through self-employment. The study aims to assess the effectiveness of the programme as far as skills training and development is concerned by assessing one of the CWP major sites in Gauteng, namely, City of Tshwane in Erasmus and two other sites in the City of Joburg in Region F and Region G. The assessment period is between 2009 and 2014. The study employed qualitative research methodology using a case study approach and focus groups to interview and engage participants in all the 3 sites. Questionnaires were developed and distributed to all participants in the study. The architects of the programme, namely leadership of the custodian department (COGTA) and other sector departments, were engaged through interviews, and their contributions were taken into consideration with a view to making recommendations on possible improvements in the programme given the history and lessons learnt. The managers of the programmes at the site level were also engaged, the CWP site project management and the Local Reference Committee (LRC) members. Findings indicates that the programme has contributed significantly towards skills development of participants and that most of the participants who exited the programme were able to find better opportunities in the labour market and a few managed to start self-employment job initiatives. The findings reveal that support for the programme should go beyond just provision of skills training opportunities but also support programmes after exiting the programme (CWP Post Programme Support). This should be infused in the exit strategy of the programme. The findings also reveals that the quality of the skills training courses provided should be improved upon and more focus and bias should perhaps be on accredited training focusing on the youth.
MM
Keywords: Economic development,Public works,Local government,Unemployment -- South Africa.